Emerging relationships between religious education and citizenship education: teachers' perceptions and political dilemmas in Cyprus - Zembylas, Michalinos ca. 20./21. Jh. (British Journal of religious education, 2018)
This article explores the ways in which a group of primary school teachers in Cyprus interprets the relationship between religious and citizenship education. The contextualisation of the meaning of religious education shows the extent to which social, historical and political elements shape teachers' perceptions about the entanglements between religious and citizenship education. In particular, the present study reveals two important findings - one concerning the conceptualisation of each school subject and their perceived relationship and the other concerning the contextualisation of this relationship in the cultural and political contexts of Cyprus. The findings also reveal important constraints and political dilemmas for the possible trajectories of religious citizenship education' in Cyprus. The article discusses the implications for curriculum and policy deliberations, as well as further research on religious citizenship education' in specific cultural and political settings.